Getting up to Speed: Assessing Usable Knowledge from Global High-Speed Rail Experience for the United States. Issue 1 (January 2015) - Perl, Anthony; Goetz, Andrew
Because the United States has taken steps in recent years to invest significant funds to implement high-speed rail, it is important to consider how high-speed rail has developed elsewhere since its original deployment between Tokyo and Osaka, Japan, in 1964. The three models of highspeed rail development that have emerged over the past 50 years are (a) the exclusive-corridor strategy exemplified by Japan, (b) the hybrid-corridor strategy found in France and Germany, and (c) the comprehensive national network strategy pioneered by China. The relevance of these three models to high-speed rail development in the United States is conditioned by several factors, including previous attempts to develop high-speed rail in the country, the institutional organization of the existing U.S. freight rail industry, and external market dynamics. Although the U.S. railroad industry has evolved differently and moved apart from rail operations in many other countries, external market dynamics such as growing urban populations and increased demand for passenger rail transportation appear to be converging with those in the rest of the world. Accordingly, several lessons are drawn for the United States from global high-speed rail experience: (a) a higher degree of relevance and higher ease in knowledge transfer would occur from following the exclusive-corridor model, (b) less difficulty in knowledge transfer but less relevance would arise in adopting the hybrid-corridor model, and (c) more relevance but more difficulty of knowledge transfer accompanies pursuit of the comprehensive national network model.